2021
DOI: 10.1002/prca.202000079
|View full text |Cite
|
Sign up to set email alerts
|

MALDI mass spectrometry imaging unravels organ and amyloid‐type specific peptide signatures in pulmonary and gastrointestinal amyloidosis

Abstract: Purpose Amyloidosis is a disease group caused by pathological aggregation and deposition of peptides in diverse tissue sites. Recently, matrix‐assisted laser desorption/ionization mass spectrometry imaging coupled with ion mobility separation (MALDI‐IMS MSI) was introduced as a novel tool to identify and classify amyloidosis using single sections from formalin‐fixed and paraffin‐embedded cardiac biopsies. Here, we tested the hypothesis that MALDI‐IMS MSI can be applied to lung and gastrointestinal specimens. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…Recently, however, other authors have proposed slightly different amyloid signatures: Misra et al ( 81 ) indicated ApoE, SAP, and glycosaminoglycans; Benson et al ( 1 ) proposed ApoE, SAP and heparan sulfate proteoglycan; Schumann et al ( 82 ), using a new proteomics approach based on MALDI imaging, have found an even more elaborate signature composed of ApoE, SAP, Apolipoprotein A-1, Vitronectin, and SAA.…”
Section: Typing Amyloidmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, other authors have proposed slightly different amyloid signatures: Misra et al ( 81 ) indicated ApoE, SAP, and glycosaminoglycans; Benson et al ( 1 ) proposed ApoE, SAP and heparan sulfate proteoglycan; Schumann et al ( 82 ), using a new proteomics approach based on MALDI imaging, have found an even more elaborate signature composed of ApoE, SAP, Apolipoprotein A-1, Vitronectin, and SAA.…”
Section: Typing Amyloidmentioning
confidence: 99%
“…Nanometric spatial resolution, however, is still impossible with MSI at its present level of development and technical improvements are needed for its successful application in clinical pathology ( 82 ).…”
Section: Typing Amyloidmentioning
confidence: 99%
“…Additional important knowledge is also being provided by another proteomic approach, MALDI imaging mass spectrometry (IMS). This technology possesses the unique capability of allowing direct MS analysis of histology sections, thereby preserving the spatial distribution of proteins [92,94,95]. MALDI-IMS studies allow demonstrating the co-localization of amyloid-associated proteins with Congo Red-positive areas, but are also disclosing differences in the peptides with which amyloid-associated species are identified in different amyloidosis types and tissues.…”
Section: The Al Amyloid Proteome: Disease Typing Characterization Of Deposited Lc Proteoforms and The Amyloid Environmentmentioning
confidence: 99%
“…MALDI-IMS studies allow demonstrating the co-localization of amyloid-associated proteins with Congo Red-positive areas, but are also disclosing differences in the peptides with which amyloid-associated species are identified in different amyloidosis types and tissues. The MALDI-IMS distribution of peptides from a set of amyloid-associated proteins (e.g., ApoE, SAP, VTN) has in fact been proposed as part of a possible strategy for amyloid typing [94], since specific peptide ions create a type and organ specific MALDI-IMS signature [95]. These observations may relate to distinct conformation, abundance or localization of these molecular species, opening unprecedented questions and new perspectives in the study of amyloidoses.…”
Section: The Al Amyloid Proteome: Disease Typing Characterization Of Deposited Lc Proteoforms and The Amyloid Environmentmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) [4,5] has recently been used to identify and characterize amyloid precursor proteins directly on thin tissue sections, such as tissue microarrays. This new technique has been used to identify systemic amyloidosis [6][7][8][9] and amyloid-β deposits in the human brain [10,11]. In Alzheimer's disease or cerebral amyloid angiopathy, the distribution of truncated C-terminal fragments of amyloid-β is altered in the brain tissue, as visualized by MALDI-Time Of Flight (TOF) MS [10,11].…”
Section: Introductionmentioning
confidence: 99%